2003
DOI: 10.1016/s0149-2063_03_00023-0
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity in Manager-Subordinate Relationships: Components, Configurations, and Outcomes

Abstract: The present study examines both positive and negative norms of reciprocity in managerial work relationships by assessing three components of reciprocal behavior: immediacy, equivalence, and interest motive. The findings show that subordinate reports of immediacy, equivalence, and self-interest were negatively associated, and mutual-interest was positively associated, with relationship quality as reported by both subordinates and managers (other-interest was not significant). These components of reciprocity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
147
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(153 citation statements)
references
References 23 publications
2
147
0
4
Order By: Relevance
“…Low-quality LMX relationships are characterized by economic exchange and feature low levels of trust, support, commitment, and loyalty (Cropanzano & Mitchell, 2005;Uhl-Bien & Maslyn, 2003). By contrast, high-quality LMX relationships increasingly engender feelings of mutual obligation and reciprocity (Liden, Sparrowe, & Wayne, 1997).…”
Section: Moderating Role Of Lmx Qualitymentioning
confidence: 99%
“…Low-quality LMX relationships are characterized by economic exchange and feature low levels of trust, support, commitment, and loyalty (Cropanzano & Mitchell, 2005;Uhl-Bien & Maslyn, 2003). By contrast, high-quality LMX relationships increasingly engender feelings of mutual obligation and reciprocity (Liden, Sparrowe, & Wayne, 1997).…”
Section: Moderating Role Of Lmx Qualitymentioning
confidence: 99%
“…According to Liden, Sparrow, and Wayne (1997): "A high-quality LMX relationship is based on social exchange, meaning that the leader and member must contribute resources valued by the other party and both parties must view the exchange as fair" (p. 50). Uhl-Bien and Maslyn (2003) differentiated between three components of reciprocal behaviour: (a) immediacy (time lapse between exchanges), (b) equivalence Relationship-based leadership 8 (equality of the exchange value to each party), and (c) interest motive (why an exchange was negotiated). In an empirical test of this perspective on reciprocity, they found that immediacy and equivalence were negatively related to follower-as well as leader-rated LMX, indicating a certain level of trust in the exchange that makes reciprocity on those dimensions less relevant.…”
Section: Brief Overview Of Lmx Theorymentioning
confidence: 99%
“…However, followers are thought to generally play a more active role in the LMX leadership process than is granted to them in more traditional leadership approaches. Thus, future research should investigate how followers can actively influence LMX excellence (Uhl-Bien & Maslyn 2003). This is especially relevant as followers are thought to benefit in varied and significant ways from a positive relationship quality with the leader (Gerstner & Day, 1997).…”
Section: Relationship-based Leadership 33mentioning
confidence: 99%
“…According to the theory, relationships and work roles are developed or negotiated over time through a series of various interactions between the leader and the follower that defines the different types of relationships: low quality and high-quality relationships (Bauer & Green, 1996). Low LMX relationships are characterised by economic exchange based mainly on formal and tangible assets, such as employment contracts and payment (Blau, 1964;Dulebohn et al, 2011), whereas people in high-quality relationships will get far more than those in low relationships, not only in terms of economic exchange, but also in social exchange; more specifically, such values as mutual trust, obligation, respect, loyalty and reciprocity will become the dominant features in the relationship (Liden & Maslyn, 1998;Uhl-Bien & Maslyn, 2003).…”
Section: Background and Development Of The Lmx Theorymentioning
confidence: 99%
“…Social exchange processes fostering relationships between leaders and followers are characterised by generalised reciprocity or mutual-interest reciprocity (Uhl-Bien & Maslyn, 2003) as argued in social exchange theory on LMX (Graen & Uhl-Bien, 1991;Wayne & Green, 1993;Erdogan & Liden, 2002). In contrast with economic exchange, Blau (1964, p. 99) argued that "only social exchange tends to engender feelings of personal obligation, gratitude, and trust; purely economic exchange as such does not."…”
Section: Background and Development Of The Lmx Theorymentioning
confidence: 99%